Analysis of Motive and Effectiveness of Norway Foreign Aid Through Redd+ Scheme on Peat Forest Restoration In Indonesia - Lucitania Rizky; Ghofur Cucucaniago (Wadah Inovasi Indonesia, 2023)
Indonesia's 22.5 million hectares of peat forest, which is capable of storing 30% of the world's carbon dioxide, has attracted Norway to provide international assistance in implementing the REDD+ scheme. This research was conducted using qualitative research methods to analyze Norway's international aid based on the concept of international aid and the effectiveness of international aid in the failure of peat forest restoration in Indonesia. Four Norwegian aid funding mechanisms through NICFI failed to reduce carbon emissions by 41%, following the provisions of the Letter of Intent (LoI) on REDD+ agreed upon by Indonesia and Norway in 2009. The reason is that Norway's national interests are mixed with international aid provided, so that is Self-Interest following the dimensions of international assistance. This also makes the effectiveness of international assistance insignificant even though it is following the five principles of the Paris Declaration on Aids Effectiveness. Keywords: REDD+, International Aid Concept, International Aid Effectiveness Concept, Funding Mechanism, Self-Interest, and Carbon Emissions